Origen via Rufinus on the New Testament Canon - Gallagher, Edmon L. (New Testament studies, 2016)
Around the turn of the fifth century Rufinus of Aquileia translated many important Greek theological works, especially by Origen and Eusebius. These translations have received a great deal of criticism for their lack of fidelity to their Vorlagen, a criticism that extends to their statements on the New Testament canon. Several scholars now assume that the list of New Testament books to be found in Origen's Homilies on Joshua 7.1 (available only in Rufinus' Latin translation) should be attributed to the translator rather than to Origen himself. This paper calls this assumption into question by comparing Eusebius' statements on the books of the New Testament to Rufinus' translation of those statements. We will find that Rufinus does, in fact, alter his text in some subtle ways so that the statements on the canon correspond more closely to the increasingly stabilised canon of the late-fourth and early-fifth centuries, but such subtle alterations do not overturn the translator's basic fidelity when reporting earlier views. This analysis suggests that Origen did produce a list of books in the mid-third century that closely - though not exactly - resembled the list of New Testament books published by Athanasius in 367.